PENGARUH PENGGUNAAN PROBLEM BASED LEARNING (PBL) DAN CONTEXTUAL TEACHING LEARNING (CTL) TERHADAP HASIL BELAJAR MATEMATIKA DITINJAU DARI MINAT BELAJAR (Studi Eksperimen pada Peserta didik Kelas VI SDN Jebres Surakarta) - Sumarmi, Dw (FKIP, PGSD, Universitas Slamet Riyadi, 2023)
The of this study istodescribe the use ofthe ProblemeBasedeLearningemodel and the ContextualeTeaching Learninge model which is reviewed from the interest in learning in grade VI students of SDN Jebres Surakarta District.